2013
DOI: 10.1007/s10815-013-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

The association of arylendosulfatase 1 (SULF1) gene polymorphism with recurrent miscarriage

Abstract: Purpose One of the most common problems in reproductive medicine is recurrent miscarriage (RM). There is increasing evidence showing genetic susceptibility of women is an important risk factor in the occurrence of RM. In recent years, there is a growing interest in sulfate and its role in fetal development. A novel mechanism of SULF1 has been demonstrated for modifying the activities of some growth factors and signalling molecules that have major roles during embryogenesis. The aim of present study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition, SULF1 haplotype ACC was associated with an increased risk of PE. A previous study showed that SULF1 rs6990375 polymorphism was related to recurrent miscarriage in Iranian women [42]. Several studies have linked SULF1 genetic polymorphisms to the risk of ovarian cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SULF1 haplotype ACC was associated with an increased risk of PE. A previous study showed that SULF1 rs6990375 polymorphism was related to recurrent miscarriage in Iranian women [42]. Several studies have linked SULF1 genetic polymorphisms to the risk of ovarian cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple SULF1 effects arise from the modulation of the BMP, Hedgehog and Wnt signaling pathways, as well as fibroblast growth factors. An association between SULF1 mutation and occurrences of recurrent miscarriage has also been postulated [ 82 ]. Thus, the detected changes in SULF1 expression patterns between physiological and FGR-complicated placentas may play an important role in the determination of this pregnancy pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A group has reported a correlation between SULF1 (rs6990375G>A) polymorphism and increased risk of recurrent miscarriage among a subpopulation of Iranian patients in which there were higher frequencies of GG and AA homozygous genotypes among patients. Moreover, higher frequency of AG genotype among healthy cases showed a correlation between this genotype and higher chance of successful pregnancy (Zahraei et al, ). Mitochondria are the cellular bioenergetic centers that have fundamental role during cell proliferation and development through oxidative phosphorylation and ATP production (Dumollard, Duchen, & Carroll, ).…”
Section: Angiogenesismentioning
confidence: 99%